KANDUNGAN PROTEIN BIJI DAN TEMPE BERBAHAN DASAR KACANG-KACANGAN LOKAL (FABACEAE) NON KEDELAI (SEEDS AND TEMPEH PROTEIN CONTENT FROM NON SOYBEAN FABACEAE) - Ervina Titi Jayanti (Bioscientist : Jurnal Ilmiah Biologi, 2019)
Soybean is the main raw material for the making of tempeh. Currently the domestic soybean production is still not able to fullfill the needs of local tempeh industry, so the fulfillment of the needs of the raw material became dependent on imports. An alternative solution that can be used to reduce the reliance of imported soybeans are against using the beans such as local hyacinth bean known as komak with brown and white seed (Lablab purpureus (L.) Sweet), kratok or komak kace (Phaseolus lunatus), gude/lebui (Cajanus cajan) as an alternative to the main raw material in the making of tempeh. This research aims to uncover the total seed protein content of the beans before  and after processed into tempeh. Protein content tests done with the Kjehdahl method, water content by the method of oven (gravimetric) as well as the ash levels with the furnice method. The results showed that there is a difference in the levels of protein content when the seed processed into tempe. The highest seed protein content owned by lebui/gude (20.90%), komak with white seed (20.26%), komak with brown color seed (20.24%), and komak kace/kratok (18.73%). After being processed into tempeh, protein content from the highest is white seed komak/hyacinth bean tempeh (14.70%), lebui tempeh (12.23%), komak kace/kratok tempeh (11,81%), and tempeh made by komak/hyacinth bean with brown seeds (9.89%).